Governing Artificial Intelligence for Educational Justice: A Critical Pedagogy and Policy Analysis in the Philippine Context - Saldivar, John Mark Navarette (Yayasan Cendekiawan Indonesia Timur, 2026)
This study examines how artificial intelligence (AI) is framed and governed within Philippine educational policy, considering its implications for equity, teacher autonomy, and learner agency. The objective is to understand the power dynamics and ideological presuppositions that inform AI-centric reforms. This research employs an integrative analytical methodology that incorporates critical policy analysis, discourse tracing, thematic coding, and ideological critique. Methodological integrity is established through rigorous inclusion and exclusion criteria, adherence to the PRISMA protocol for systematic document review, and the application of the CASP Checklist to assess the credibility and pertinence of 21 significant policy documents published between 2021 and 2025. The findings reveal that prevailing policies primarily depict AI as a tool for modernization, operational efficiency, and data-driven governance. At the same time, critical concerns regarding ethics, human rights, and democratic participation remain insufficiently addressed. These accounts pose a substantial risk of exacerbating existing inequalities between well-resourced and under-resourced educational institutions. In response, the study advocates for the ARISE Framework (AI Rights-based Inclusive Systems for Education). This nascent governance model prioritizes structural preparedness, pedagogical agency, critical scrutiny of AI discourses, and rights-centric oversight. The study emphasizes the imperative of equity impact assessments, transparency requirements, accountability systems, and the continuous development of critical AI literacy among educators and students. These initiatives ensure that AI integration aligns with Sustainable Development Goal 4, thereby reinforcing rather than undermining equitable and inclusive educational opportunities.